ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO CANDI MUARA JAMBI BERBASIS SEJARAH LOKAL PADA MATA KULIAH SEJARAH INDONESIA - Nur Agustiningsih; Satriyo Pamungkas (Universitas Negeri Padang, 2018)
The development of technology and communication has a big influence on all fields of life including in the field of education. Creativity and innovation is needed in developing learning media including in learning history. The purpose of this research is to obtain: 1) description of the use of learning media in the learning process in the field, 2) obstacles faced by lecturer in Indonesian history up to the 15th century learning 3) media formulations needed in learning Indonesian History. This research is a qualitative descriptive research. Data collection techniques used are interviews, observation and analysis of documents. The informan were selected through purposive sampling. Data validation used triangulation. Data analysis techniques used interactive analysis models including data collection, data reduction, data presentation and conclusion drawing. The result of the research shows that 1) Lecturer has used learning media as a learning resource in the learning process, but are still less varied. The media used is still limited to the use of powerpoint which displays images and text only. 2) The constraints faced by the lecturer in delivering the material about the muara jambi temple are limited references and learning resources. 3) Media that needs to be developed in learning is video